A’dan Z’ ye Girişimsel Radyoloji - Tokur, Oğuzhan; Kesimal, Uğur; Güneş, Yasin Celal; Yılmaz, Berkay; Korkmazer, Bora; Yıldırım, Mustafa; Çayhan, Velihan; Önder, Ramazan Orkun; Akış, Serhat; Özer, Törehan; Ak, Büşra; Demirci, Mehmet Gürdal; et al. (Academician Publishing Book DOI Portal, 2024)
-